Study of Allosteric Transitions of Human P-Glycoprotein by Using the Two-State Anisotropic Network Model - Li, Hongwu; Gong, Weikang (Frontiers in Medicine, 2022)
Human P-glycoprotein is a kind of the ATP-binding cassette transporter. Once human P-glycoprotein is over expressed in tumor cells, it can lead to tumor multidrug resistance. However, the present experimental methods are difficult to obtain the large-scale conformational transition process of human P-glycoprotein. In this work, we explored the allosteric pathway of human P-glycoprotein from the inward- to outward-facing state during the substrate transport process with the two-state anisotropic network model. These results suggest that the allosteric transitions proceed in a coupled way. The conformational changes of nucleotide-binding domains finally make the transmembrane domains to outward-facing state via the role of allosteric propagation of the intracellular helices IH1 and IH2. Additionally, this allosteric pathway is advantageous in energy by comparing with other methods. The study reveals the conformational transition of P-glycoprotein, contributes to understanding the allosteric mechanism of ATP-binding cassette exporters.